ANALISA YURIDIS PENEGAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA KORUPSI PADA PENYUSUNAN MASTER PLAN KOTA MEDAN TAHUN 2006 – 2016 - Jadiaman Sinaga (USU LAW JOURNAL, 2013)
Abstract The principle of criminal’s responsibility in criminal law is based on the guilt (schuld) in the action against the law (wederechtelijk) as a requirement for the imposition of criminal (grenzen van delictsomschrijving, wederrechtelijk is en aan schuld te wijten). One of them is the Decision of “Tipikor” (Criminal Act of Corruption) Court related to the corruption of Medan Master Plan of 2006-2016 stating that the element of “enriching” cannot be proven as primary charge. The problems discussed in this study including the kind of criminal act of corruption, responsibility and punishment for the corruptor in the preparation of Medan Master Plan of 2006-2016. The data for this normative legal study with statute approach were the secondary data obtained through library research in the forms of legal materials related to the law enforcement on the case of corruption in the procurement of consulting services during the preparation of Medan Master Plan of 2006 – 2016 at the Tipikor Court of Medan State Court. All of the data obtained were qualitatively analyzed. The preparation of Medan Master Plan of 2006 – 2016, the opinion of the panel of judges, the primary charges, especially related to the element of benefitting oneself or any other person or corporation as meant by Article 2 paragraph (1), was not proven, but the subsidiary charge as meant by Areticle 3 of Law No.31/1999 juncto law No. 20/2001 on Corruption Eradication. Keywords: Criminal Law Enforcement, Criminal Act of Corruption, 2006-2016 Medan Master Plan Preparation